29) replace Y in the 2nd equation with the first equation and solve:
4x -3(2x-3) = 31
distribute the -3(2x-3)
4x-6x+9 = 31
combine 4x-6x
-2x +9 = 31
subtract 9 from each side
-2x = 22
divide both sides by -2 to get x
x = 22 / -2 = -11
x = -11
now replace x in the first equation with -11 to solve for y
y = 2(-11) -3
y = -22 -3
y = -25
x = -11, y = -25 which is (-11,-25) so A is the correct answer
30) the solution is where the 2 lines cross which is at X = 2 and Y = 4 which is (2,4) so B is the correct answer